2018
DOI: 10.1177/1559325818774977
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Antagonizes TNF-α-Induced L929 Fibroblastoma Cells Apoptosis by Inhibiting NF-κBp65 Activation

Abstract: Paeoniflorin (PF) is one of the main pharmacodynamic components of Paeonia suffruticosa Andr, which has a significant anti-inflammatory effect on rheumatoid arthritis (RA), with a mechanism related to the tumor necrosis factor α (TNF-α). The aim of the present study was to investigate the role of PF in the apoptosis and expression of NF-κBp65 of L929 fibroblastoma cells induced by TNF-α. Our results showed that different concentrations of PF can significantly reduce the growth inhibition of L929 cells. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Ferulic acid promotes osteogenesis in bone marrow mesenchymal stem cells and suppresses osteoclast differentiation (Du et al, 2017; Doss et al, 2018). Paeoniflorin has a significant anti-inflammatory effect on rheumatoid arthritis (Lai et al, 2018; Xu et al, 2018). Paeoniflorin also shows antiosteoporosis activity and regulates osteoclastogenesis and osteoblastogenesis (Li and Chent 2018b; Wang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Ferulic acid promotes osteogenesis in bone marrow mesenchymal stem cells and suppresses osteoclast differentiation (Du et al, 2017; Doss et al, 2018). Paeoniflorin has a significant anti-inflammatory effect on rheumatoid arthritis (Lai et al, 2018; Xu et al, 2018). Paeoniflorin also shows antiosteoporosis activity and regulates osteoclastogenesis and osteoblastogenesis (Li and Chent 2018b; Wang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…A previous in vivo study demonstrated that paeoniflorin, the main component of SYGCT, dose-dependently decreases the secretion of pro-inflammatory mediators by inhibiting the activation of nuclear factor kappa light chain enhancer in B cells p65 (NF-κB/p65). 23 As to the prescription of GLY, a mechanistic study in a rat model revealed that the anti-inflammatory activity of GLY may be tied to the inhibition of pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α, and PGE2. 24 One former study using an animal experimental model also found that an extract of Magnolia officinalis, a major ingredient purified from PWS, could substantially regulate the production of inflammatory mediators by abating the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…According to the protocol delineated by Vanlangenakke et al ( 2011 ), the cells were treated with 50 μl of CJ flower extract at varying concentrations (1, 5, 10, 50, and 100 μg/ml) alongside 50 μl of H 2 O 2 (250 μM) for a 24-h duration. Subsequently, cell viability was assessed using the MTT assay, and the cell viability was calculated based on the absorbance, as outlined by Lai et al ( 2018 ). The experiment was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%